Azithromycin consideration in the phase 1 therapy of uncontrolled Diabetes Mellitus with severe generalised chronic periodontitis - A case report - Yaacob, Munirah (2012)
Periodontitis is the commonest oral manifestation found in Diabetes Mellitus (DM) patients. Conventional treatment of scaling and root planning (SRP) in DM patients with periodontitis may be an effective way of treating the disease. However, the prediction of exponential increase of DM worldwide would requisite a more efficacious, promising and time savings management to increase the capacity of treatment provided and dental health in this group. In this instance, antibiotics would be considered the best adjunct to SRP. This case was treated in 2010. The patient was 53 years, British, Male, with 15 years chronic history of Uncontrolled DM Type II. He had experienced tooth loss since 40’s plus frequent oral infections. However the main complaint was tooth migration. Random blood sugar (RBS) was 11 mmol/l at time. The baseline examination revealed multiple teeth loss with deep pockets average of 10mm at majority of sites. Prognosis of multiple teeth was considered poor and required extraction. The diagnosis of Generalised Severe Chronic Periodontitis was made. The patient had undergone a cycle of full mouth SRP with Azithromycin 500mg for 3 days. Re-evaluation at 3 months revealed complete resolution of all deep pockets with only few sites with 4 or 5mm and healthier appearance of gingiva. The RBS was 7mmo/l at time. The combination of Azithromycin seems promising to treat severe periodontitis despite the poor glycemic control in this patient. The reduction of level of RBS may be an indirect positive effect due to resolution of periodontitis.